Patients With Natural Killer (NK) Cell Chronic Active Epstein-Barr Virus Have Immature NK Cells and Hyperactivation of PI3K/Akt/mTOR and STAT1 Pathways. (9th May 2020) - Howe, Matthew K; Dowdell, Kennichi; Kuehn, Hye Sun; Li, Qingxue; Hart, Geoffrey T; Garabedian, Doreen; Liepshutz, Kelly; Hsu, Amy P; Su, Hua; Niemela, Julie E; Stoddard, Jennifer L; Uzel, Gulbu; et al.
Abstract: Background: Chronic active Epstein-Barr virus (CAEBV) presents with high levels of viral genomes in blood and tissue infiltration with Epstein-Barr virus (EBV)–positive lymphocytes. The pathogenesis of CAEBV is poorly understood. Methods: We evaluated 2 patients with natural killer (NK) cell CAEBV and studied their NK cell phenotype and signaling pathways in cells. Results: Both patients had increased numbers of NK cells, EBV predominantly in NK cells, and immature NK cells in the blood. Both patients had increased phosphorylation of Akt, S6, and STAT1 in NK cells, and increased total STAT1. Treatment of 1 patient with sirolimus reduced phosphorylation of S6 in T and B cells, but not in NK cells and did not reduce levels of NK cells or EBV DNA in the blood. Treatment of both patients' cells with JAK inhibitors in vitro reduced phosphorylated STAT1 to normal. Patients with T- or B-cell CAEBV had increased phosphorylation of Akt and S6 in NK cells, but no increase in total STAT1. Conclusions: The increase in phosphorylated Akt, S6, and STAT1, as well as immature NK cells describe a new phenotype for NK cell CAEBV. The reduction of STAT1 phosphorylation in their NK cells with JAK inhibitors suggests a novel approach to therapy. Abstract : Patients with natural killer (NK) cell chronic active Epstein-Barr virus disease were found to have increased activation of Akt, S6, and STAT1 in their NK cells as well as large increases in immature NK cells in the blood.